Strategi Pengelolaan Lingkungan RSUD Rokan Hulu Menuju Green Hospital - Megariani Megariani; Ridwan Manda Putra; Bayhakki Bayhakki (SEHATI: Jurnal Kesehatan, 2023)
The purpose of this study was to estimate the existing conditions of Rokan Hulu Hospital in an effort to apply the principles of green hospital and determine strategy for managing the hospital's environment towards green hospital. Hospitals have a positive impact on a good quality of life, but also have the potential to be the biggest source of pollution to the surrounding environment. This study uses a qualitative approach with descriptive research methods. The results showed that the Rokan Hulu Hospital only met the requirements for implementing the Green Hospital elements at 27.9%, which is still relatively low. Based on the SWOT analysis, the environmental management strategy that can be carried out by Rokan Hulu Hospital towards green hospital is in quadrant I, namely supporting an aggressive strategy by implementing an SO (Strenghts-Opportunities) strategy, which was utilizing all strengths as much as possible by taking advantage of existing opportunities . The strategy that can be carried out at Rokan Hulu Hospital is to improve the performance of hospital leadership and staff in developing the green hospital concept technology-based waste, establishing cooperation with relevant agencies or stakeholders, developing green open land that already exists as an attraction for hospitals.